WFP Cash, Food, and Voucher Study in Ecuador - International Food Policy Research Institute (International Food Policy Research Institute, 2011)
This study is a cluster-randomized controlled evaluation of a transfer program linked to preschool participation. The transfer program, administered by the World Food Programme, provides food or cash transfers to children aged 3-5 years enrolled in preschools at baseline. The preschools, operating in the Karamoja sub-region of Uganda, are supported by UNICEF and managed by District representatives of the Government of Uganda. The food transfers consist of multiple-micronutrient-fortified corn soy blend (CSB), oil, and sugar, totaling approximately 1200 calories per day per child and including 99% of iron requirements. Cash transfers equal the estimated value of the food basket if purchased in the market. Randomization into the food treatment, cash treatment or control was done across 98 preschools, referred to as Early Childhood Development (ECD) centers. The intervention period was from February 2011 to May 2012 and included distribution of transfers on a six-to-eight-week cycle. A longitudinal (panel) survey of households with children aged 3-5 years at baseline was conducted before exposure to the transfers and 18 months later. The randomized design of this effectiveness study and the panel nature of the data allow for a rigorous field trial in which impacts on nutrition and cognitive outcomes can be assessed and compared across modalities.We examine the impacts of the two transfer modalities, cash transfers or multiple-micronutrient-fortified food transfers, linked to preschool enrollment, on child nutrition and cognitive development. In addition, we explore potential mechanisms through intermediate impacts on food intake and participation in preschools.The key research objectives are to assess the following:Impacts on targeted groups: Assess the effects of cash or food transfers on nutrition and cognitive outcomes in children aged 3-5 years at baseline and explore pathways for these effects.Optimal program design: Assess the differential impacts of a program in which children are provided multiple-micronutrient-fortified food transfers linked to preschool enrollment compared with one in which they are given the equivalent value of cash transfers linked to preschool enrollment.